Volume 3: 38th Design Automation Conference, Parts a and B 2012
DOI: 10.1115/detc2012-71176
|View full text |Cite
|
Sign up to set email alerts
|

Consider-Then-Choose Models in Decision-Based Design Optimization

Abstract: This article describes an advance in design optimization that includes consumer purchasing decisions. Decision-Based Design optimization commonly relies on Discrete Choice Analysis (DCA) to forecast sales and revenues for different product variants. Conventional DCA, which represents consumer choice as a compensatory process through maximization of a smooth utility function, has proven to be reasonably accurate at predicting choice and interfaces easily with engineering models. However the marketing literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…The more flexible mixed and nested logit models did not offer meaningful improvements for the new vehicle market using the types of covariates that have been used in the literature, although we only examined mixed logit models with diagonal covariance matrices. We caution that these types of models may not be well suited to predict vehicle shares for new design or policy evaluation [7,[9][10][11] and that these same limitations may apply to other product design domains which use discrete choice models [4][5][6]. Reducing the data set to include only midsize vehicles improved the predictive capabilities of the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more flexible mixed and nested logit models did not offer meaningful improvements for the new vehicle market using the types of covariates that have been used in the literature, although we only examined mixed logit models with diagonal covariance matrices. We caution that these types of models may not be well suited to predict vehicle shares for new design or policy evaluation [7,[9][10][11] and that these same limitations may apply to other product design domains which use discrete choice models [4][5][6]. Reducing the data set to include only midsize vehicles improved the predictive capabilities of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MacDonald et al suggest that consumers' preferences for attributes do not exist a-priori but rather that products are evaluated on a case by case basis [56]. Morrow et al [10] and others have suggested that vehicle choice behavior may be better represented by a consider-then-choose model where consumers do not maximize their utility over the universe of available choices but rather screen all choices to narrow them down to a reasonable subset over which utility maximization applies. And more broadly, the Lucas critique warns against use of aggregated historical data to predict outcomes in counterfactual future scenarios [70].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Ref. [54], this technique does not easily generalize to other problems. The contours of the objectives, the budget constraint, and the optimal solutions for Scenarios (1) and (2) are illustrated in Fig.…”
Section: Consumer Choice Modelsmentioning
confidence: 99%
“…(22)- (28) or with other techniques; e.g., see Ref. [54]. Because of this flexibility in solution technique, it is useful to state important technical results in terms of Eq.…”
Section: Acknowledgmentmentioning
confidence: 99%